Abitare e produrre. Ripensare lo spazio con Martin Heidegger e Henri Lefebvre - Spina, Salvatore (Mechane, 2023)
The aim of this paper is to provide a critical analysis of the relationship between Martin Heidegger and Henry Lefebvre’s thought starting from their conception of space. I will try to show how their reflections about the space, despite some substantial differences, have the same goal. Starting from a critical analysis of cartesian ontology, they try to develop a new idea of space beyond the conception of empty and neutral space typical of the analytic geometry. For that purpose, they coin two new concepts, that reveal the roots of their thought. Heidegger uses the expression “inhabiting the space” to show the ontological character of his conception of space; Lefebvre analyzes the idea of ‘production of space’ to underline the political nature of his argument.